2022
DOI: 10.3390/s22072792
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality (AR) and Cyber-Security for Smart Cities—A Systematic Literature Review

Abstract: Augmented Reality (AR) and cyber-security technologies have existed for several decades, but their growth and progress in recent years have increased exponentially. The areas of application for these technologies are clearly heterogeneous, most especially in purchase and sales, production, tourism, education, as well as social interaction (games, entertainment, communication). Essentially, these technologies are recognized worldwide as some of the pillars of the new industrial revolution envisaged by the indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 61 publications
(96 reference statements)
0
30
0
Order By: Relevance
“…From the point of view of navigation in the pathway, because it configures inputs, it delivers complete control to the learner, and the teacher configures their role as the mediator between the pathway and the learner [ 29 ]. Regarding the learning outcome, the study has revealed a relationship between the implementation of the learning itinerary, mediated by AR, for the mechatronics course and the learning outcomes [ 30 , 31 ]. Finally, it is essential to emphasize the contribution of this research in terms of scientific references that establish a relationship between the use of personal learning itineraries and augmented reality in the training of students, where academic performance is improved in addition to the research process.…”
Section: Discussionmentioning
confidence: 99%
“…From the point of view of navigation in the pathway, because it configures inputs, it delivers complete control to the learner, and the teacher configures their role as the mediator between the pathway and the learner [ 29 ]. Regarding the learning outcome, the study has revealed a relationship between the implementation of the learning itinerary, mediated by AR, for the mechatronics course and the learning outcomes [ 30 , 31 ]. Finally, it is essential to emphasize the contribution of this research in terms of scientific references that establish a relationship between the use of personal learning itineraries and augmented reality in the training of students, where academic performance is improved in addition to the research process.…”
Section: Discussionmentioning
confidence: 99%
“…ICTs are not without their challenges; they have spawned cybersecurity concerns. Although augmented reality (AR) and cyber-security technologies have been around for a while, of late, they have experienced exponential growth [70,71]. Augmented reality will be an integral part of the digital infrastructure of smart cities in the years to come [72].…”
Section: Augmented and Virtual Reality (Ar/vr) In Smart Citiesmentioning
confidence: 99%
“…By enabling smart transactions through smart contracts and decentralized applications, blockchain provides a high degree of autonomy for the operation of smart cities [ 37 ]. Additionally, research is being conducted on cybersecurity issues related to the use of augmented reality (AR) technologies in smart cities [ 38 ].…”
Section: Key Elements Of Smart Citiesmentioning
confidence: 99%